(untitled) - Shelly, Gary B.; Gary B. Shelly; Thomas J. Cashman; Misty E. Vermaat (Boston, Mass. ; London, 2007)
Provides a current and thorough introduction to computers by integrating usage of the World Wide Web with the printed text. Updated for currency, this Shelly Cashman Series text offers a complete solution to successfully teach students basic computer concepts with new exercises, case studies, and online tools on the Online Companion
Keywords: Computers; Computer science; Computer networks